The Ambivalent Role of the EU in the Western Balkans – “Limited Europeanisation” between Formal Promises and Practical Constrain - Iordan Gheorghe Bărbulescu; Miruna Troncotă (Romanian Journal of European Affairs)
It became a shared opinion among European policy-makers to state that without a serious commitment from the European Union (EU), the Western Balkans (WB) will find itself increasingly isolated from the unfolding developments around it and this may endanger the stability of the entire continent. The scope of this paper is two folded: first, to examine the role of the EU in the WB with a focus on democratic institution-building; second, taking Bosnia-Herzegovina (BiH) as a case study, the article aims to determine whether there is a need for a new theoretical framework in order to more accurately define the specific process of the Europeanisation in the WB. In this regard it proposes the term “limited Europeanisation”. The main theoretical aim of the article is to identify some clear-cut criteria of this phenomenon in the last 14-year evolution of BiH in relation with the EU.